The influence of the work environment and work motivation on the performance of agricultural training center employees Ministry of Agriculture of the Republic of Indonesia - Dhia, Muhammad Rafi (MID Publisher International, 2024)
This study examines the impact of the work environment and motivation on employee performance at the Agricultural Training Center, run by the Agricultural Extension and Human Resources Development Agency of the Ministry of Agriculture in Indonesia. An associative quantitative technique was used to investigate the correlations between these factors, using data obtained from 37 workers by questionnaire. The findings show that both the work environment and motivation substantially and positively affect employee performance. Specifically, the work environment and motivation each showed t-values exceeding critical thresholds, with a combined F-value that supports a substantial impact on performance. The implications suggest that organizations can enhance employee performance by improving the work environment and strengthening motivational practices. It is recommended that management continue to foster a supportive work environment and implement strategies to maintain high employee motivation, such as providing recognition, incentives, and opportunities for career development. Further research could include a larger, more diverse sample to validate the findings and explore other factors influencing employee performance.